Remote rendering control using Python scripts and Dropbox technology - Bernik, Andrija (Array, 2018)
The process of rendering a 3D animation often takes a very long time to complete. In situations where it would take several hours or even many days, it is inconvenient to spend that time near the rendering computer in order to control and oversee the process. Through the work with 3D computer graphic technologies, the authors realized that there is no simple solution on the market that facilitates the monitoring of the remote computer that is running the rendering process. This paper deals with developing a system to enable those tasks to be done from a remote computer or any mobile device. The developed proof-of-concept system consists of two Python programs communicating over the Dropbox service and a computer that is running the Autodesk Maya software.